Individual biosafety barrier in dentistry: an alternative in times of covid-19. Preliminary study - MONTALLI,Victor Angelo Martins (2020)
ABSTRACT The return to dental practice in pandemic times is a new challenge due to the generation and dispersion of droplets and aerosols that may contain the SARS-CoV-2 virus, the etiological agent of covid-19. In the last months some droplet and aerosol containment strategies have been circulating on the internet, however, until now there is no evidence in the literature to prove the effectiveness of such barriers. Thus, using a microbial dispersion model with the fast handpiece, the aim of this preliminary study was to compare the dispersion caused by the the dental drill (DD) alone or in association with an individual biosafety barrier (IDBD / DD), which consisted of a layer of PVC film combined to a layer of polypropylene mounted on a frame. The dental drill was activated for one minute having had the water from the reservoir been replaced with a suspension of Lactobacillus casei Shirota. Petri dishes containing MRS agar were positioned at 50, 100 and 150 cm from the headboard of the dental chair at different angles (90 and 0 degrees). At 50 cm, the mean (standard deviation) of L. casei Shirota for DD was 13,554.59 (493.48) CFU, while for IDBD / DD was 570.67 (60.54) CFU (p <0.0001), establishing a 96% reduction. Considering these preliminary results, the individual biosafety barrier proved effective in reducing dispersion from the dental drill in this study model, which suggests that this barrier may be a viable option to optimize biosafety in the dental environment.